Maximal oxygen uptake versus maximal power output in children - Dencker, M.; Thorsson, O.; Karlsson, M. K.; Linden, K.; Wollmer, P.; Andersen, L. B. (Journal of Sports Sciences, 2008)
Maximal oxygen uptake (VO2max) is considered the optimal method to assess aerobic fitness. The measurement of VO2max, however, requires special equipment and training. Maximal exercise testing with determination of maximal power output offers a more simple approach. This study explores the relationship between VO2max and maximal power output in 247 children (139 boys and 108 girls) aged 7.9-11.1 years. Maximal oxygen uptake was measured by indirect calorimetry during a maximal ergometer exercise test with an initial workload of 30 W and 15 W/min increments. Maximal power output was also measured. A sample (n = 124) was used to calculate reference equations, which were then validated using another sample (n = 123). The linear reference equation for both sexes combined was: VO2max (ml/min) = 96 + 10.6 · maximal power + 3.5 · body mass. Using this reference equation, estimated VO2max per unit of body mass (ml/min·kg) calculated from maximal power correlated closely with the direct measurement of VO2max (r = 0.91, P <0.001). Bland-Altman analysis gave a mean limits of agreement of 0.2±2.9 (ml/min·kg) (1 s). Our results suggest that maximal power output serves as a good surrogate measurement for VO2max in population studies of children aged 8-11 years.